2018
DOI: 10.1515/jisys-2016-0073
|View full text |Cite
|
Sign up to set email alerts
|

An Approach to Detect Vehicles in Multiple Climatic Conditions Using the Corner Point Approach

Abstract: This paper presents a new method of detecting vehicles by using a simple and effective algorithm. The features of a vehicle are the most important aspects in detection of vehicles. The corner points are considered for the proposed algorithm. A large number of points are densely packed within the area of a vehicle, and the points are calculated by using the Harris corner detector. Making use of the fact that they are densely packed, grouping of these points is carried out. This grouping indicates that the group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…Each traffic image in the convolution neural network determines these regions after applying graphical and parallel detection and recognition by utilizing efficient and parallel pre-processing means. More recent research related to the motivation of the manuscript can be found in references [ 21 , 22 ].…”
Section: The Related Workmentioning
confidence: 99%
“…Each traffic image in the convolution neural network determines these regions after applying graphical and parallel detection and recognition by utilizing efficient and parallel pre-processing means. More recent research related to the motivation of the manuscript can be found in references [ 21 , 22 ].…”
Section: The Related Workmentioning
confidence: 99%
“…To detect triangular and rectangular symbols, Anandhalli and Baligar [15] applied the Harris corner detector to the ROIs, searched for corners in the predefined control area. Li [16] relied on edge information to recognize traffic signs that are difficult to detect in the driving environment: Based on the shape features of scale-invariant edge turning angles, the nonparametric shape detector was used to detect circles, triangles, and rectangles in the image; more than 95% of all traffic signs were covered by this detector.…”
Section: A Shape-based Traffic Sign Recognitionmentioning
confidence: 99%
“…Once the detected vehicles are verified then the centroid of the object or the interest points of the objects are passed to the CNN. The CNN will help in reliable tracking of the vehicles even though the occlusion, shadows appear in the image [23][24].…”
Section: Corner Pointsmentioning
confidence: 99%
“…To enhance the performance, CNN is utilized for classification and recognition of the image. CNN includes lakhs of different images of different class [10][11]. CNN is used to extract information of image and to study complicated features.…”
mentioning
confidence: 99%